2007
DOI: 10.1016/j.bbrc.2007.03.168
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin upregulates its receptors and inhibits lipolysis and leptin release in male rat adipose tissue

Abstract: Prolactin (PRL) is recognized as a metabolic regulator during lactation, but little information exists on its actions in male adipose tissue. We examined whether PRL affects the expression of its receptors (PRLR), lipolysis and adipokine secretion in male rats. Both long and short PRLR isoforms were induced 40 to 50-fold during differentiation of epididymal preadipocytes, with a 10 fold higher expression of the long isoform. PRL upregulated both isoforms before and after differentiation. PRL suppressed lipolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…However, results of recent studies suggest that the response is reciprocal in both directions, since on the one hand it has been found that leptin regulates DA in response to sustained stress and eating behavior in humans, implicating involvement of DAergic pathways in this response, 34,35 and on the other hand a study in an experimental model showed that prolactin inhibits lipolysis and leptin release. 36 These discrepancies may be due to several factors, such as doses of DA and prolactin, experimental design, species, or sex. …”
mentioning
confidence: 99%
“…However, results of recent studies suggest that the response is reciprocal in both directions, since on the one hand it has been found that leptin regulates DA in response to sustained stress and eating behavior in humans, implicating involvement of DAergic pathways in this response, 34,35 and on the other hand a study in an experimental model showed that prolactin inhibits lipolysis and leptin release. 36 These discrepancies may be due to several factors, such as doses of DA and prolactin, experimental design, species, or sex. …”
mentioning
confidence: 99%
“…In all, our data suggest that hypophysectomy-induced effects on Rab18 mRNA expression may be mediated by the decrease in circulating thyroid hormones resulting from the lack of pituitary TSH. Nonetheless, we cannot exclude the possibility that other pituitary hormones (or lack thereof) not investigated in this study and known to act on adipose tissue, such as PRL (Brandebourg et al 2007), might also be responsible, at least in part, for the effects observed in hypophysectomized animals.…”
Section: Discussionmentioning
confidence: 87%
“…Although the majority of experimental studies have demonstrated the effect of prolactin in increasing leptin expression and secretion [36,37], data regarding an influence of leptin on prolactin production have been lacking. Therefore, future research is necessary to clarify the relationship between prolactin and leptin serum levels in euprolactinemic subjects.…”
Section: Discussionmentioning
confidence: 99%